Marchantia polymorpha : Studi Profil dan Kandungan Senyawa Bioaktif Potensial sebagai Obat di Masa Mendatang - Farhan, Abdillah Maulana; Masayu, Muhammad Zulfikar Arian; Azizah, Alya Najwa; Risqi, Alexandria Zazila; Shodiq, Abdulloh Hasan; Shodiq, Muhammad Husein (Jurnal Penelitian Sains, 2025)
Marchantia polymorpha is one type of liverwort thallus. This liverwort has three subspecies: M. polymorpha subsp. polymorpha, M. polymorpha subsp. ruderalis, and M. polymorpha subsp. montivagans. These three subspecies exhibit different morphologies and have their own characteristics. M. polymorpha subsp. polymorpha is characterized by a thick black line running down the center of the thallus to the tip, while M. polymorpha subsp. ruderalis has a broken central line on the thallus, and M. polymorpha subsp. montivagans has no central line on its thallus. M. polymorpha contains bioactive compounds that have potential medicinal properties. Analysis using GC-MS indicates that there are 10 dominant compounds in this liverwort, with 8 of them being potentially beneficial for health, acting as antimicrobials, anticancer agents, anti-inflammatory agents, and having other biological activities. The aim of this study is to explore further information regarding the profile and bioactive compound content of M. polymorpha using a literature or secondary data approach. The benefits of this study are to advance the stages of primary research and to provide an overview of the morphology, distribution, life cycle of the liverwort, the content of its compounds, and its potential as a medicine in the future.